Treatment of biliary leakages after cholecystectomy and importance of stricture development in the main bile duct injury - Erkan PARLAK,; Bahattin ÇİÇEK,; Selçuk DİŞİBEYAZ,; Sedef ÖZDAL KURAN,; Dilek OĞUZ,; Burhan ŞAHİN, (Turkish Journal of Gastroenterology, 2019)
-